An optimal modulation strategy for minimising the losses of isolated multisource DC-DC converters - Fischer, C.; Mariethoz, S.; Morari, M. (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society, 2012)
The paper investigates optimal modulation of isolated two-quadrant and multisource DC-DC converters. Due to their numerous degrees of freedom there are infinitely many possibilities to modulate the voltage patterns in order to achieve the desired power transfer. The objective of this work is to exploit this flexibility to derive a modulation strategy that minimises the system power losses. A systematic modelling and optimisation approach is proposed that allows to minimise the overall losses subject to constraints on particular devices. The obtained optimal modulation angles are stored in look-up tables. The impact of the transformer leakage inductance on the efficiency is investigated, which gives some indications on how to design the transformer. Effectiveness of the approach is demonstrated in simulation.